1998
DOI: 10.2307/2463574
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Symmetry and Sexual Selection: A Meta-Analysis

Abstract: A considerable body of primary research has accumulated over the last 10 yr testing the relationship between developmental instability in the form of fluctuating asymmetry and performance of individuals in mating success itself or sexual attractiveness. This research comprises 146 samples from 65 studies of 42 species of four major taxa. We present the results of a meta-analysis of these studies, which demonstrates that there is indeed an overall significant, moderate negative relationship: for studies, the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 0 publications
0
89
1
Order By: Relevance
“…As we touched on above, there is a large body of literature indicating that humans tend to be drawn to others who are more physically attractive. The origination of this phenomenon has been debated by psychologists of different origin; it may have an evolutionary beginning (attractiveness indicative of health and reproductive success; Moller & Thornhill, ) or it may be based, at least in part, from social learning at a very young age (Eagly et al., ). However, either origin leads to the conclusion that quite often there is a positive affective reaction to an attractive person and a negative affective reaction to an unattractive person (Lucker, Beane, & Helmreich, ).…”
Section: Mediating Mechanisms: Attributions and Likingmentioning
confidence: 99%
“…As we touched on above, there is a large body of literature indicating that humans tend to be drawn to others who are more physically attractive. The origination of this phenomenon has been debated by psychologists of different origin; it may have an evolutionary beginning (attractiveness indicative of health and reproductive success; Moller & Thornhill, ) or it may be based, at least in part, from social learning at a very young age (Eagly et al., ). However, either origin leads to the conclusion that quite often there is a positive affective reaction to an attractive person and a negative affective reaction to an unattractive person (Lucker, Beane, & Helmreich, ).…”
Section: Mediating Mechanisms: Attributions and Likingmentioning
confidence: 99%
“…Possible sources are genetic disturbances, toxics, and a high exposure to and/or a limited capacity to withstand parasites (see Thornhill and Moller 1997 for a review). Along the same line, Moiler and Thornhill (1998) provide meta-analytic evidence that, in many species, body symmetry is a valid cue for mate value that is utilized in mate choice. Concerning humans, several studies indicate that facial symmetry is positively linked to facial attractiveness (Grammer and Thornhill 1994;Hume and Montgomerie 2001;Mealey et al 1999;Rhodes et al 1998;Scheib et al 1999;Zebrowitz et al 1996; but also see Fink et al 2001;Rhodes et al 2001;Rikowski and Grammer 1998;Shackelford and Larsen 1997;Swaddle and Cuthill 1995 for mixed or contradictory results).…”
Section: Symmetry As a Signal Of Qualitymentioning
confidence: 99%
“…It has been established that humans prefer symmetrical patterns in numerous domains (Little et al 2007; Reber et al 2004), and preference for symmetrical visual features has been observed in creatures as simple as the bumblebee (Moller and Thornhill 1998; Rodriguez et al 2004). The widespread and robust influence of symmetry on aesthetic preference has resulted in several theories of its biological significance.…”
mentioning
confidence: 99%